Clinical features and prognostic predictors of C. Psittaci Pneumonia: a systematic review and individual patient meta-analysis - Qingqing Jia; Jibo Sun; Dongguang Wang; Jiao Xu; Xiu Li; Shijie Zhang; Lian Wang; Sitong Liu; Xiang Tong; Hong Fan (BMC Pulmonary Medicine)
Abstract Background The clinical presentations and prognostic indicators of C. psittaci pneumonia are inadequately investigated currently. The objective of the study was to assess the clinical presentation of C. psittaci pneumonia and the risk factors for severe pneumonia, within a systematic review and individual patient meta-analysis. Methods We searched PubMed, CNKI, and Wanfang databases for case reports/series of proven/probable psittacosis published between 1st January 2000 and 28th February 2023, including all hospitalized individuals aged ≥ 18 years. Patient demographics, manifestations, diagnostic methods, and outcomes were summarized descriptively. Patients were divided into severe or non-severe pneumonia groups mainly according to the ATS/IDSA 2007 criteria. Prognostic predictors for severe C. psittaci pneumonia were identified using multivariate logistic regression. Results 3062 articles of 196 (566 individual patient cases) were included in the final analysis. Patients with chronic cardiovascular disease face a significantly elevated risk of developing severe C. psittaci pneumonia (adjusted odds ratio (aOR) 2.63; 95% confidence interval (CI) 1.05–6.59; P = 0.039). Symptoms including dyspnea (aOR 4.88; 95% CI 3.19–7.46; P < 0.001), neuropsychiatric symptoms (aOR 3.58; 95% CI 2.05–6.28; P < 0.001), gastrointestinal symptoms (aOR 1.76; 95% CI 1.10–2.80; P = 0.018), or the presence of multilobar infiltrates on imaging (aOR 3.27; 95% CI 2.11–5.06; P < 0.001) upon admission frequently serve as indicators of severe pneumonia. Conclusions Chronic cardiovascular disease increases susceptibility to severe C. psittaci pneumonia. The presence of dyspnea, neuropsychiatric symptoms, gastrointestinal symptoms, and multilobar infiltrates upon admission merits clinicians’ attention, advocating for timely sample submission for metagenomic next-generation sequencing (mNGS) to ascertain the etiology.